Meta Analysis: Application of Health Belief Model on the Tertiary Prevention of Type 2 Diabetes Mellitus - Etanaulia Marsim; Fara Aristya Prisma; Herawati Prianggi (Journal of Health Promotion and Behavior, 2021)
Background: Diabetes Mellitus Type 2 is a hyperglycemic disease due to insensitivity of cells to insulin. Insulin levels may decrease slightly or be in the normal range. The level of adherence of type 2 diabetes patients is lower than type 1 diabetes. Compliance with medication and taking medication in DM patients has a very important role in controlling blood sugar levels. HBM is a model that describes a person's knowledge of health threats and understanding of recommended behaviors to prevent or treat health problems based on an assessment of feasibility and benefits compared to costs. This study aimed to estimate the effect of HBM, especially the severity and self-efficacy constructs.Subjects and Method: This study was conducted using a systematic review and meta-analysis study design using PICO. Population: type-2 diabetic patients. Intervention: high severity perception and high self-efficacy. Comparison: low severity perception, and low self-efficacy. Outcome: tertiary prevention behaviors. The articles used in this study came from 4 databases, namely Google Scholar, Pubmed, Science Direct and Proquest. The article keywords are “health belief model” OR “perceived severity” OR “self-efficacy” AND “type 2 diabetes”. The articles included in this study are full paper articles, cross-sectional study designs, 2012-2021 and the size of the relationship between Adj Odds Ratio. Article selection is done using PRISMA. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 12 cross-sectional studies were reviewed in this study. A meta-analysis of 7 cross-sectional studies showed that strong perceived severity increased the likelihood of implementing tertiary prevention behaviors in type 2 diabetes patients by 4.69 times (aOR= 4.69; 95% CI= 1.92 to 11.47; p= 0.007). A meta-analysis of 9 cross-sectional studies showed that slightly stronger perceived self-efficacy increased the likelihood of implementing tertiary prevention behaviors in type 2 diabetes patients by 1.68 times (aOR= 1.68; 95% CI= 1.03 to 2.74; p= 0.040).Conclusion: Severity perception and self-efficacy are predictors for tertiary prevention of type 2 Diabetes Mellitus.Keywords: predictors, tertiary prevention, type-2 diabetes mellitus, health belief model.Correspondence:Etanaulia Marsim. Health Polytechnics, Ministry of Health, Surakarta. Jl. Letjen Sutoyo, Mojosongo, Kota Surakarta, Jawa Tengah. Email: etanaulia@gmail.com. Mobile: +6285840530580.Journal of Health Promotion and Behavior (2021), 06(04): 284-297DOI: https://doi.org/10.26911/thejhpb.2021.06.04.03